Study of Collagenase-3 Levels in Rheumatoid Arthritis Patients with and without Type 2 Diabetes Mellitus - Abdul_Zahra, Nadia Abdul_Kareem; Al-Rubaei, Zainab M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
This research sought early signs of type 2 diabetes mellitus (T2DM) in rheumatoid arthritis (RA) patients. The current research's objectives are to identify collagenase-3 (CL-3) in RA patients with and without T2DM as a disease complication, compare these findings to those of a control group, and ascertain whether or not CL-3 correlates with all of the parameters that were examined in each group. In the present research, (150) participants all between the ages of 30 and 50 were divided into three groups: (G1) control (N=50), (G2) RA (N=50), and (G3) RA with T2DM (N=50). Collagenase-3, glycated hemoglobin (HbA1c), erythrocyte sedimentaion (ESR), anti-cyclic citrullinated peptide (anti-CCP), and rheumatoid factor (RF) were all measured in this experiment. Data revealed that (G2) and (G3) had considerably greater RF, anti-CCP, and ESR levels than (G1) in comparison. Compared to G2, there was a very obvious increase in G3. The results of the HbA1c test showed that (G2) increased non-significantly compared to (G1), but (G3) was much more than (G2) and (G1). The levels of CL-3 in (G2) and (G3) were found to be significantly higher than in controls (G1) in these groups. A well-related biomarker with these patients was shown by CL-3, demonstrating a strong positive or negative association with all metrics for all groups. This suggests that the best medicine and therapy will be available for these patients. These results suggest that CL-3 might be a biochemical diagnostic for RA patients' early diagnosis of diabetes.